Risk of Spread of Megalocytivirus pagrus1 (Infectious Spleen and Kidney Necrosis Virus) From Frozen Fillets - Joy A. Becker; Paul M. Hick; Dorothea Megarani; Hannah Siler; Felipe Pierezan; Shannon N. Gray; Kuttichantran Subramaniam (Journal of Fish Diseases, 2026)
Infectious spleen and kidney necrosis virus (ISKNV) is a significant threat to global aquatic food security by causing large‐scale mortality in the aquaculture of tilapia ( Oreochromis niloticus ) and mandarin fish ( Siniperca chuatsi ). ISKNV is a genogroup of Megalocytivirus pagrus1 , along with RSIV and TRBIV, and their recent listing as WOAH‐notifiable diseases highlights the need to assess spread pathways to prevent exotic pathogen incursions. An albino rainbow shark ( Epalzeorhynchos frenatum ) challenge model was used to evaluate the risk of ISKNV introduction from the trade in frozen seafood products by determining viability after freezing and the median infectious dose (ID 50 ). Six donor fish were injected with ISKNV with tissues collected after clinical signs appeared and used immediately or stored at −20°C for 7 days. Challenge inocula were prepared consisting of snout, eyes, and brain (Pool A; representative of head‐on eviscerated fish products), caudal skin and muscle (Pool B; representative of skin‐on fillet only products) or peritoneal viscera (Pool C; positive control group). Fish were challenged by bath immersion or intraperitoneal injection and sampled for ISKNV detection by qPCR at morbidity/death, or on Day 14. Negative control fish all survived without detection of ISKNV. All tissue pools including ‘skin‐on fillet only’ caused infection and disease via IP injection or immersion, whether used fresh or frozen, showing ISKNV remains infectious after 7 days at −20°C. The model estimated an ID 50 of 42 ISKNV genome equivalents (95% CI: 19–98). This study is the first to investigate the potential for ISKNV spread via frozen fish products, a commodity frequently traded in international markets. The findings provide evidence to inform import risk assessments and highlight the need for further investigation into spread pathways involving uncooked, frozen fish products.